OPTIMALISASI PATROLI RODA DUA SATSAMAPTA GUNA MENCEGAH PENCURIAN KENDARAAN BERMOTOR DI WILAYAH POLRES BREBES - Denzel Andersson Cahyono Cahyono (Police Studies Review, 2022)
OPTIMIZATION OF THE SAMAPTA TWO WHEEL PATROL TO PREVENT MOTOR VEHICLE THEFT IN JURISDICTIONS OF BREBES POLICE RESORT DENZEL ANDERSSON CAHYONO, 18.066, denzelcahyono@gmail.com The author's final project raises the issue of "How to Optimize the Implementation of the Two-Wheel Patrol of the Samapta Unit to Prevent Motor Vehicle Theft in the Brebes Police Area?". This final project aims to compare theory and practice on the implementation of two-wheeled patrols and find efforts to optimize the implementation of two-wheeled patrols carried out by the Brebes Police Headquarters in order to prevent the crime of theft in the jurisdiction of the Brebes Police. This research uses a qualitative approach with the type of case study research by conducting limited observations, interviewing resource persons and reviewing documents. This study uses management theory and competency theory as well as the concepts contained in the laws and regulations governing the Satsamapta two-wheeled patrol procedure. The Brebes Police Samapta Unit in carrying out two-wheeled patrols to prevent theft is still not in accordance with the SOP. In its implementation, two-wheeled patrols are not in accordance with the division of patrol hours and patrol teams that have been determined. The patrols carried out are still in the form of a combination of two-wheeled vehicles and four-wheeled vehicles. The patrol route that was determined was only based on initial data from the Brebes Police Intelligence Unit and not based on the development of the security situation and conditions in the field. The leadership's supervision of the implementation of the two-wheeled patrol of the Brebes Police Satsamapta is still relatively low. The competence possessed by members of the Brebes Police Satsamapta in carrying out two-wheeled patrols is still very minimal, seen from the number of personnel who have attended vocational education, especially in the field of patrolling and there are still members who commit several violations in carrying out their duties. For this reason, efforts are needed to optimize the implementation of the two-wheeled patrol of the Brebes Police Satsamapta in preventing theft by providing a reward and punishment system for members, enforcing SOPs for the implementation of two-wheeled patrols, improving organizational management, providing training for members, and strengthening supervision from the leadership. Keyword : Samapta two-wheeled patrol, Samapta Unit, motor vehicle theft, Optimization